2011
DOI: 10.1002/cjs.10114
|View full text |Cite
|
Sign up to set email alerts
|

Fitting regression models with response‐biased samples

Abstract: This paper extends the work in Lawless, Kalbfleisch, & Wild (1999) on fitting regression models with response‐biased samples, that is, samples where some or all the covariates are missing for some units and the probability that this happens depends in part on the value of the reponse of that unit. In general, the resulting likelihood depends on the distribution of the covariates but we are only interested in methods that do not involve modelling this distribution. We look at a variety of methods based on estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 30 publications
1
43
0
Order By: Relevance
“…Scott and Wild [35] recently suggested estimating the sampling probabilities π that occur in the second term of the PL equations (2) using a parametric model π ( y , x;α ) = Pr( R = 1 |y , x;α ), as has just been illustrated for WL. Denote the PL equations with estimated π by S 0 ( β , α ) and let…”
Section: Accounting For More Of the Phase I Informationmentioning
confidence: 99%
See 3 more Smart Citations
“…Scott and Wild [35] recently suggested estimating the sampling probabilities π that occur in the second term of the PL equations (2) using a parametric model π ( y , x;α ) = Pr( R = 1 |y , x;α ), as has just been illustrated for WL. Denote the PL equations with estimated π by S 0 ( β , α ) and let…”
Section: Accounting For More Of the Phase I Informationmentioning
confidence: 99%
“…Scott and Wild [35] also suggested that additional information about α might be obtained from the PL equations with estimated weights by solving the system…”
Section: Accounting For More Of the Phase I Informationmentioning
confidence: 99%
See 2 more Smart Citations
“…Regression analysis under informative sampling is, in particular, an important topic in this area. See Chambers (2003), Pfeffermann and Sverchkov (2009), Scott and Wild (2011), Kim and Skinner (2013), and references therein.…”
Section: Introductionmentioning
confidence: 99%